2015
DOI: 10.1136/bmjquality.u208167.w3252
|View full text |Cite
|
Sign up to set email alerts
|

Keeping patients with epilepsy safe: a surmountable challenge?

Abstract: This quality improvement project was inspired as an answer to a problem that intellectual disability teams have been struggling to manage whilst caring for people with epilepsy (PWE). The issue was that despite guidance to discuss the possibility of sudden unexpected death in epilepsy (SUDEP) be discussed with a newly diagnosed PWE this is rarely done. Additionally when, how, and what to discuss about SUDEP and reduce its risk is arbitrary, non-person centred, and with no structured evidence.Prior to initiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Rates of seizure-related deaths and SUDEP correlate with increased seizure frequency and insufficient engagement with clinicians [28] , [20] , [21] , [22] , [23] , [40] , [41] . Without appropriate medical attention, indicators that point to an increased likelihood of premature mortality may not be identified, restricting the ability to intervene [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Rates of seizure-related deaths and SUDEP correlate with increased seizure frequency and insufficient engagement with clinicians [28] , [20] , [21] , [22] , [23] , [40] , [41] . Without appropriate medical attention, indicators that point to an increased likelihood of premature mortality may not be identified, restricting the ability to intervene [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The findings recommend that SUDEP information includes prevalence, risk factors, and risk reduction methods. Although not specific to CYPwE, the SUDEP and seizure safety checklist developed by Shankar et al has been found to encourage healthcare professionals to discuss SUDEP with their patients [35]. It takes approximately 10-minutes to complete [36] and allows a risk assessment to be conducted, providing an individualised SUDEP risk rating which can be used to begin discussions about SUDEP and to provide a tailored risk reduction plan involving lifestyle modifications such as medication compliance and nighttime surveillance [37].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 17 factors remained well associated with SUDEP and are directly relevant for people living with epilepsy. These 17 factors forms the background of the Seizure and SUDEP safety checklist, a 10 minute risk assessment tool used in epilepsy clinics across UK and the selfmonitoring of epilepsy risk mobile app EpSMon 5,6,7 . We compared these 17 factors between the 48 subjects who died from SUDEP in Cornwall with 220 of 231 continuous patients living with epilepsy who attended local outpatient epilepsy clinics to determine how strongly these factors are associated with SUDEP risk in a well defined population.…”
Section: Introductionmentioning
confidence: 99%